An overview on the design, operation and levelized costs of hydrogen refuelling stations for fuel cell electric vehicles / Tajul Farhan Tamimuddin, WANW Mohamed and MFA Yaziz @ Mohamad - Tamimuddin, Tajul Farhan; Mohamed, WANW; Yaziz @ Mohamad, MFA (Smart Manufacturing Research Institute (SMRI), 2024)
Interest in hydrogen economy is developing rapidly and spearheaded by developed countries to mitigate the combined effects of volatile fossil fuel market and environmental pollution. The transportation sector is a key area in the transition from fossil-based fuels to a clean hydrogen fuel. Fuel cell electric vehicle (FCEV) technology has matured and successfully tested on a wide range of transportation platforms. To enable FCEV as commercially viable, an important factor is the availability of hydrogen refuelling stations (HRS) at fuel cost that is affordable. This article provides a general overview of hydrogen transportation economy for stakeholders, policymakers, and investors to facilitate informed decision-making. It explores the expansion of HRS designs and operation based on the emphasis on green energy concepts towards achieving improvements in the Levelized Cost of Hydrogen (LCOH). It is acknowledged that the success of a green HRS operation in meeting targeted LCOH is highly dependent on the cost of the energy source, where solar and wind power are the current central solutions. LCOH is seeing a visible reduction as the new cost-effective technologies emerge, as well as greater emphasis is given on optimizing the operation. The review concluded that green HRS is capable of meeting a commercially attractive LCOH within five to ten years mainly through the optimization of operation strategy.